The Evolution of the Teacher's Role in the Technology Era: A Literature Study on the Adaptation of Teaching in the Development of the Digital Age - Marselina, Suci; Prananda, Gingga; Judijanto, Loso; Fauzi, Muhammad Sukron; Hendra, Muhammad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to explore the evolution of the teacher's role in the technological era, specifically in the context of teaching adaptation in the digital age. Through a literature review approach, this study analyzes various relevant literatures on how technology has changed the way teachers interact with students and design learning. The main findings indicate that the teacher's role has transformed from a traditional instructor to a more dynamic and interactive learning facilitator, thanks to the use of technology. However, challenges such as limited digital skills among teachers and infrastructure gaps remain significant barriers to the implementation of technology in the classroom. Additionally, this study found that the use of models such as SAMR can guide teachers in integrating technology more innovatively. The study concludes that to maximize the benefits of technology in education, teachers need to continuously develop their digital skills through ongoing training and enhance educational infrastructure equitably.